Counseling On The Introduction Of Sharia Bank To Al-Utsaimin Bangkinang-Kampar It High School Students - Khairi, Rifqil; Mairiza, Diany; Zakir, Muhammad; Winario, Mohd; Amalia, Nala (Journal of Community Sustainability, 2024)
This service is carried out for Al-Utsaimin IT High School students. The aim of this community service is to determine the level of understanding of Al-Utsaimin IT High School students regarding the development of sharia banking products in Indonesia. The methods used in this community service activity are counseling, presentations and discussions. The results of the service show that: The service program for the students of SMA IT Al-Utsaimin can be organized well and run smoothly in accordance with the activity plan that has been prepared. The results of this service conclude that: First, the students of SMA IT Al-Utsaimin have an understanding of bank development Sharia in Indonesia varies, some already understand it, some are still doubtful, some even don't understand it. Second, the achievement of the objectives of the service activity program for Al-Utsaimin IT High School students, the entire program has been carried out in collaboration between business owners and The service has all been carried out and in accordance with the event rounddown and predetermined time.